High-barrier adhesive film for perovskite battery as well as preparation method and application of high-barrier adhesive film

By adding high-barrier masterbatches to the POE resin of perovskite batteries, the problem of perovskite batteries being sensitive to water, oxygen and ultraviolet rays is solved, and the long-term aging stability and power generation efficiency of the battery are achieved.

CN119391329AInactive Publication Date: 2025-02-07ZHEJIANG SINOPONT TECH

Patent Information

Application Number
CN202411975416.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Perovskite batteries are sensitive to water, oxygen, and ultraviolet rays, resulting in material decomposition in a comprehensive stress environment of light, water and oxygen, resulting in battery failure and power attenuation.

Method used

A high-barrier masterbatch is added to the POE resin, which contains a water-blocking POE resin, an oxygen-blocking glyceryl auxiliaries, and an UV absorber that blocks UVB to form a glue film that can block water, oxygen and ultraviolet rays simultaneously .

Benefits of technology

It achieves the maintenance of long-term aging stability of perovskite batteries while ensuring the power generation efficiency of perovskite batteries, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of packaging adhesive films, and discloses a high-barrier adhesive film for a perovskite battery as well as a preparation method and application of the high-barrier adhesive film for the perovskite battery, the high-barrier adhesive film comprises the following raw materials: 80-95 parts of POE resin, 5-20 parts of high-barrier master batch and 0-2 parts of auxiliaries; the high-barrier master batch is prepared from the following raw materials in parts by weight: 100 parts of POE resin, 1 to 10 parts of oxygen barrier additive, 1 to 10 parts of UVB ultraviolet absorbent and 0.01 to 0.2 part of organic peroxide. According to the invention, the high-barrier master batch is added into the POE resin, and the master batch simultaneously contains the water-blocking POE resin, the oxygen-blocking olefine acid glyceride oxygen barrier additive and the ultraviolet absorbent for blocking UVB, so that the long-term aging stability of the perovskite battery can be maintained while the power generation efficiency of the perovskite battery is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging adhesive films, and in particular to a high-barrier adhesive film for perovskite cells, and a preparation method and application thereof. Background Art

[0002] With the rapid development of the photovoltaic industry, cells are constantly being updated, from the early development of polycrystalline silicon and monocrystalline silicon, to the second generation of flexible batteries and thin-film batteries, and then to the new third generation of perovskite cells. Perovskite cells have attracted much attention due to their high photoelectric conversion efficiency, simple preparation process and low cost. However, the stability of perovskite cells has always restricted its commercialization process. As we all know, perovskite cells are sensitive to water, oxygen, and ultraviolet rays. Especially in the combined stress environment of light, water, and oxygen, it is easy for materials to decompose, resulting in battery failure and severe power attenuation. This is the biggest challenge facing perovskite cells. Therefore, the high barrier design of encapsulation film for perovskite cells has become an important technical means to solve this problem.

[0003] POE resin itself has a very low water vapor permeability, and is a very good water barrier material, but has a high oxygen permeability. Generally, oxygen barriers use high oxygen barrier EVOH materials, but due to the high crystallinity and low light transmittance of EVOH, it is not suitable for film materials that require high light transmittance. In addition, the melting point of EVOH is higher than 150°C, which is much higher than the requirement of less than 125°C during perovskite cell film lamination, and is not suitable for perovskite encapsulation film materials. Summary of the invention

[0004] The present invention aims to overcome the problem that the POE adhesive film in the prior art cannot simultaneously meet the high barrier properties for water, oxygen and ultraviolet rays, and provides a high barrier adhesive film for perovskite cells, a preparation method thereof and an application thereof. A high barrier masterbatch is added to the POE resin, and the masterbatch simultaneously contains a water-blocking POE resin, an oxygen-blocking olefinic glyceride auxiliary agent, and an ultraviolet absorber for blocking UVB, so that the long-term aging stability of the perovskite cell can be maintained while ensuring the power generation efficiency of the perovskite cell.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a high-barrier adhesive film for a perovskite battery, wherein the raw materials include 100 parts of POE resin, 5 to 20 parts of high-barrier masterbatch and 0 to 2 parts of an auxiliary agent in parts by weight; The raw materials of the high barrier masterbatch include: 100 parts of POE resin, 1-10 parts of oxygen barrier additives, 1-10 parts of UVB ultraviolet absorbers and 0.01-0.2 parts of organic peroxides; the oxygen barrier additive is at least one of glyceryl arachidonic acid ester, docosahexaenoic acid glyceryl monoester, 1-stearic acid-2-arachidonic acid glyceryl ester, and 2-arachidonic acid glyceryl ester-D5.

[0006] The adhesive film of the present invention adds a high-barrier masterbatch to the POE resin, and the high-barrier masterbatch also contains functional additives that block water, oxygen, and ultraviolet rays. The POE matrix material in the high-barrier masterbatch is a low water permeability material with excellent water vapor barrier performance; the olefinic glyceride oxygen barrier additive used in the present invention also contains multiple hydroxyl bonds, has strong polarity, is incompatible with oxygen, and is easy to block oxygen; and contains multiple double bonds, which can be grafted onto the POE resin for fixation and is not easy to migrate; the use of UVB-cutoff ultraviolet absorbers can not only absorb the most energetic and most harmful UVB ultraviolet rays, but also keep the UVA part as highly permeable as possible, without affecting the power generation efficiency of the perovskite battery. Therefore, the adhesive film of the present invention can simultaneously meet the high barrier requirements for water, oxygen, and ultraviolet rays, and can maintain the long-term aging stability of the perovskite battery while ensuring the power generation efficiency of the perovskite battery.

[0007] Preferably, the auxiliary agent includes 0-1 part of light stabilizer and 0-1 part of tackifier in parts by weight.

[0008] Preferably, the light stabilizer is one or more of UV-292, UV-622, and UV-770.

[0009] Preferably, the tackifier is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinylsilane oligomer, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane.

[0010] Preferably, the organic peroxide is at least one of tert-butyl peroxide 2-ethylhexyl carbonate, tert-amyl peroxide 2-ethylhexyl carbonate, tert-butyl peroxide-3,5,5-trimethylhexanoate, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, di-tert-amyl peroxide, and 2,5-dimethyl-2,5-bis-(tert-butyl peroxy)hexane.

[0011] Preferably, the weight of the high barrier film for perovskite battery is 80-600 g / cm 2 .

[0012] In a second aspect, the present invention provides a method for preparing the above-mentioned high barrier film for perovskite battery, comprising the following steps: (1) Preparation of high barrier masterbatch: POE resin, oxygen barrier additive, UVB ultraviolet absorber and organic peroxide are mixed in proportion, melt-extruded and pelletized to obtain high barrier masterbatch; (2) Preparing a high-barrier adhesive film for perovskite batteries: POE resin, high-barrier masterbatch and additives are mixed in proportion, and melt-extruded and cast to obtain the high-barrier adhesive film for perovskite batteries.

[0013] Preferably, the extrusion temperature in step (1) is 130-180°C; and the extrusion temperature in step (2) is 110-180°C.

[0014] In a third aspect, the present invention provides an application of the above-mentioned high-barrier adhesive film for perovskite cells in a photovoltaic module, wherein the photovoltaic module comprises, arranged in order from top to bottom: front glass, perovskite solar cells, the high-barrier adhesive film for perovskite cells and back glass.

[0015] Therefore, the present invention has the following beneficial effects: (1) Adding a high-barrier masterbatch containing functional additives that block water, oxygen, and ultraviolet rays to the film can ensure the power generation efficiency of the perovskite battery while maintaining the long-term aging stability of the perovskite battery; (2) The glycerol ester oxygen barrier additive in the high barrier masterbatch contains multiple hydroxyl bonds, has strong polarity, is incompatible with oxygen, and is easy to block oxygen; and contains multiple double bonds, which can be grafted onto the POE resin for fixation, and is not easy to migrate, so that the POE film has a good oxygen barrier effect. DETAILED DESCRIPTION

[0016] The present invention is further described below in conjunction with specific implementation methods.

[0017] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.

[0018] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with specific implementation methods, but it should be understood that these descriptions are only to further illustrate the features and advantages of the present invention rather than to limit the claims of the present invention.

[0019] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0020] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0021] Overall embodiment: A high-barrier adhesive film for perovskite batteries, wherein the raw materials include 80-95 parts of POE resin, 5-20 parts of high-barrier masterbatch and 0-2 parts of auxiliary agent in parts by weight; The raw materials of the high barrier masterbatch include: 100 parts of POE resin, 1-10 parts of oxygen barrier additives, 1-10 parts of UVB ultraviolet absorbers and 0.01-0.2 parts of organic peroxides; the oxygen barrier additive is at least one of glyceryl arachidonic acid ester, docosahexaenoic acid glyceryl monoester, 1-stearic acid-2-arachidonic acid glyceryl ester, and 2-arachidonic acid glyceryl ester-D5.

[0022] As a specific implementation, the auxiliary agent includes 0-1 part of light stabilizer and 0-1 part of tackifier in parts by weight.

[0023] As a specific implementation, the light stabilizer is one or more of UV-292, UV-622, and UV-770.

[0024] As a specific embodiment, the tackifier is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinylsilane oligomer, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane.

[0025] As a specific embodiment, the UVB ultraviolet absorber is at least one of 2-hydroxy-4-n-octyloxybenzophenone, ethylhexyl triazone, pentaerythritol tetra(2-cyano-3,3-diphenylacrylate), 3,3,5-trimethylcyclohexanol salicylate, ethylhexyl salicylate, octyl methoxycinnamate, N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, PABA ethylhexyl ester, 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 4-methylbenzylidene camphor.

[0026] As a specific embodiment, the organic peroxide is at least one of tert-butyl peroxide 2-ethylhexyl carbonate, tert-amyl peroxide 2-ethylhexyl carbonate, tert-butyl peroxide-3,5,5-trimethylhexanoate, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, di-tert-amyl peroxide, and 2,5-dimethyl-2,5-bis-(tert-butyl peroxy)hexane.

[0027] As a specific embodiment, the weight of the high barrier film for perovskite battery is 80-600 g / cm 2 .

[0028] The method for preparing the high barrier film for perovskite battery comprises the following steps: (1) Preparation of high barrier masterbatch: POE resin, oxygen barrier additive, UVB ultraviolet absorber and organic peroxide are mixed in proportion, melt-extruded and pelletized to obtain high barrier masterbatch; (2) Preparing a high-barrier adhesive film for perovskite batteries: POE resin, high-barrier masterbatch and additives are mixed in proportion, and melt-extruded and cast to obtain the high-barrier adhesive film for perovskite batteries.

[0029] As a specific implementation, the extrusion temperature in step (1) is 130-180°C.

[0030] As a specific implementation, the extrusion temperature in step (2) is 110-180°C.

[0031] Embodiment 1: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of glycerol arachidonic acid ester, 5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite cells: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0032] Embodiment 2: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 1 part of glycerol arachidonic acid ester, 1 part of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.01 part of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 80 parts of POE resin, 20 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0033] Embodiment 3: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 10 parts of glycerol arachidonic acid ester, 10 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.2 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 95 parts of POE resin, 5 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0034] Embodiment 4: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of glycerol arachidonic acid ester, 5 parts of pentaerythritol tetra(2-cyano-3,3-diphenylacrylate), and 0.1 parts of tert-amyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of vinyl trimethoxysilane, and 0.2 parts of light stabilizer UV-292; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0035] Embodiment 5: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of glycerol arachidonic acid ester, 5 parts of 3,3,5-trimethylcyclohexanol salicylate, and 0.1 parts of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-isocyanate propyltrimethoxysilane, and 0.2 parts of light stabilizer UV-622; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0036] Embodiment 6: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of docosahexaenoic acid monoglyceride, 5 parts of 3,3,5-trimethylcyclohexanol salicylate, and 0.1 parts of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-isocyanate propyltrimethoxysilane, and 0.2 parts of light stabilizer UV-622; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0037] Embodiment 7: A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of 2-arachidonic acid glyceryl ester-D5, 5 parts of 3,3,5-trimethylcyclohexanol salicylate, and 0.1 parts of 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite battery: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-isocyanate propyltrimethoxysilane, and 0.2 parts of light stabilizer UV-622; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0038] Comparative Example 1 (without adding glyceryl arachidonic acid ester): A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, and melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite cells: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0039] Comparative Example 2 (too much addition of glyceryl arachidonic acid ester): A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 20 parts of glycerol arachidonic acid ester, 5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite cells: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0040] Comparative Example 3 (replacing glyceryl arachidonate with glyceryl undecylenate): A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of glycerol undecylenate, 5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite cells: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2 High barrier film for perovskite batteries.

[0041] Comparative Example 4 (replacing arachidonic acid glyceryl ester with arachidonic acid triglyceride): A method for preparing a high-barrier adhesive film for a perovskite battery, comprising the following steps (the amount of each substance is in parts by weight): (1) Preparation of high barrier masterbatch: 100 parts of POE resin (Sumitomo, GH030), 5 parts of arachidonic acid triglyceride, 5 parts of 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 0.1 parts of tert-butyl peroxide 2-ethylhexyl carbonate were introduced into a twin-screw extruder through a loss-in-weight scale, melt-extruded and pelletized at a temperature of 150°C to obtain a high barrier masterbatch; (2) Preparation of high-barrier adhesive film for perovskite cells: Weigh 90 parts of POE resin, 10 parts of high-barrier masterbatch, 0.5 parts of 3-methacryloxypropyltrimethoxysilane, and 0.2 parts of light stabilizer UV-770; inject all the above materials into a mixer and mix at high speed for 12 hours. After the additives are completely absorbed, cast extrusion is performed at 100°C to obtain a film with a gram weight of 400 g / cm 2High barrier film for perovskite batteries.

[0042] Application examples: The photovoltaic module is prepared using the high-barrier adhesive film for perovskite cells prepared in the above embodiments and comparative examples, and the steps are as follows: stacking the back glass, the high-barrier adhesive film for perovskite cells, the perovskite solar cell and the front glass in sequence; then placing them in a laminator for heating, vacuuming, laminating (temperature 120°C), maintaining the pressure and then taking them out for cooling to obtain a photovoltaic module.

[0043] The photovoltaic modules prepared above were subjected to UV60kWh and DH1000h aging tests. The test results are shown in Table 1.

[0044] Table 1: Photovoltaic module aging test results

[0045] As can be seen from Table 1, the high barrier films prepared by the formula of the present invention in Examples 1 to 5 have lower power attenuation at UV60kWh and DH1000h because the high barrier masterbatch contains a POE resin matrix that blocks water, an olefinic glyceride oxygen barrier aid that blocks oxygen, and a functional aid that blocks UVB ultraviolet rays. Compared with other examples, the total addition amount of oxygen barrier aid and UVB absorber in Example 2 is low, and the power attenuation at UV60kWh and DH1000h is relatively high.

[0046] However, no oxygen barrier additive was added to the high barrier masterbatch in Comparative Example 1, and the oxygen barrier performance of the film decreased, resulting in a sharp increase in the power attenuation of the components UV60kWh and DH1000h.

[0047] In Comparative Example 2, too much glycerol arachidonic acid ester was added to the high-barrier masterbatch, which resulted in poor dispersibility due to the high concentration, thereby affecting the oxygen barrier performance of the film, causing the power attenuation of the components UV60kWh and DH1000h to be higher than that of Examples 1 and 3.

[0048] In Comparative Example 3, glycerol arachidonate in the high-barrier masterbatch was replaced with glycerol undecylenate. Since glycerol undecylenate has only one double bond, the grafting efficiency during the masterbatch grafting process is reduced, resulting in a low amount of effective additives grafted on the high-barrier masterbatch, making the power attenuation of the components UV60kWh and DH1000h higher than that in Example 1.

[0049] In Comparative Example 4, glycerol arachidonic acid ester in the high barrier masterbatch is replaced with arachidonic acid triglyceride. Since arachidonic acid triglyceride lacks hydroxyl groups, its oxygen barrier performance is lower than that of glycerol arachidonic acid ester. Therefore, the power attenuation of the components UV60kWh and DH1000h is higher than that of Example 1.

[0050] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solutions, which should be included in the scope of the claims of the present invention.

Claims

1. A high barrier film for perovskite battery, characterized in that: In parts by weight, the raw materials include 80-95 parts of POE resin, 5-20 parts of high barrier masterbatch and 0-2 parts of additives; The raw materials of the high barrier masterbatch include: 100 parts of POE resin, 1-10 parts of oxygen barrier additives, 1-10 parts of UVB ultraviolet absorbers and 0.01-0.2 parts of organic peroxides; the oxygen barrier additive is at least one of glyceryl arachidonic acid ester, docosahexaenoic acid glyceryl monoester, 1-stearic acid-2-arachidonic acid glyceryl ester, and 2-arachidonic acid glyceryl ester-D5.

2. The high barrier film for perovskite battery according to claim 1, characterized in that: In parts by weight, the auxiliary agent includes 0-1 part of light stabilizer and 0-1 part of tackifier.

3. The high barrier film for perovskite battery according to claim 2, characterized in that: The light stabilizer is one or more of UV-292, UV-622 and UV-770.

4. The high barrier film for perovskite battery according to claim 2, characterized in that: The tackifier is one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl silane oligomer, 3-methacryloxypropyl trimethoxy silane, 3-methacryloxypropyl triethoxy silane, 3-(acryloxy)propyl trimethoxy silane, 3-(2,3-epoxypropoxy)propyl trimethoxy silane, 3-(2,3-epoxypropoxy)propyl triethoxy silane, 3-isocyanate propyl trimethoxy silane, and 3-isocyanate propyl triethoxy silane.

5. The high barrier film for perovskite battery according to claim 1, characterized in that: The UVB absorber is at least one of 2-hydroxy-4-n-octyloxybenzophenone, ethylhexyl triazone, pentaerythritol tetra(2-cyano-3,3-diphenylacrylate), 3,3,5-trimethylcyclohexanol salicylate, ethylhexyl salicylate, octyl methoxycinnamate, N-(2-ethoxyphenyl)-N'-(2-ethylphenyl)-oxalamide, PABA ethylhexyl ester, 3,5-di-tert-butyl-4-hydroxybenzoic acid-2,4-di-tert-butylphenyl ester, and 4-methylbenzylidene camphor.

6. The high barrier film for perovskite battery according to claim 1, characterized in that: The organic peroxide is at least one of tert-butyl peroxide 2-ethylhexyl carbonate, tert-amyl peroxide 2-ethylhexyl carbonate, tert-butyl peroxide-3,5,5-trimethylhexanoate, 1,1-di-tert-butyl peroxide-3,3,5-trimethylcyclohexane, di-tert-amyl peroxide, and 2,5-dimethyl-2,5-bis-(tert-butyl peroxy)hexane.

7. The high barrier film for perovskite battery according to claim 1, characterized in that: The high barrier film for perovskite battery has a gram weight of 80-600 g / cm 2 .

8. A method for preparing a high barrier film for a perovskite battery as claimed in any one of claims 1 to 7, characterized in that: The steps include: (1) Preparation of high barrier masterbatch: POE resin, oxygen barrier additive, UVB ultraviolet absorber and organic peroxide are mixed in proportion, melt-extruded and pelletized to obtain high barrier masterbatch; (2) Preparing a high-barrier adhesive film for perovskite batteries: POE resin, high-barrier masterbatch and additives are mixed in proportion, and melt-extruded and cast to obtain the high-barrier adhesive film for perovskite batteries.

9. The method for preparing a high barrier film for a perovskite battery according to claim 8, characterized in that: The extrusion temperature in step (1) is 130-180°C; the extrusion temperature in step (2) is 110-180°C.

10. A use of the high barrier film for perovskite cells as claimed in any one of claims 1 to 7 in a photovoltaic module, characterized in that: The photovoltaic module comprises, arranged in order from top to bottom: front glass, perovskite solar cell, high-barrier adhesive film for the perovskite cell and back glass.

Citation Information

Patent Citations

  • High-moisture and oxygen barrier property EVA adhesive film for solar module packaging and preparing method of high-moisture and oxygen barrier property EVA adhesive film

    CN104449436A

  • High-barrier full-biodegradable mulching film and preparation method thereof

    CN118063941A

Cited By

  • Graft copolymer resin for packaging adhesive film, packaging adhesive film as well as preparation method and application of graft copolymer resin

    CN121181783A